UJI EKSPERIMENTAL EFEK TWIST 180˚ TERHADAP PERFORMA TURBIN HIDROKINETIK SAVONIUS TORNADO - Punu, Andri Krismantoro; Nindito, Dwi Anung; Kamiana, I Made (Fakultas Teknik Universitas Palangka Raya, 2024)
The problem of increasing energy demand must be balanced with energy production. The development of water-powered energy is one alternative solution for the sustainability of life on earth. The Savonius Hydrokinetic Turbine is a type of hydroelectric power plant that can convert kinetic energy into electrical energy. River currents as a renewable energy source can rotate the turbine and convert it into electricity through a generator. This study aims to determine the effect of a 180˚ twist change on the Savonius Tornado Helical Hydrokinetic Turbine with a variation of the lower end plate smaller than the upper end plate. The research method was carried out by testing 4 turbine variations, namely the Savonius Hydrokinetic Turbine and the Savonius Tornado Helical Hydrokinetic Turbine D / 2, 3D / 4 and 4D / 4, where D is the diameter of the turbine end plate. The testing process was carried out in an open prismatic channel with variations in flow speed of 0.331 m / s, 0.396 m / s and 0.486 m / s. The results of the study showed that the Savonius Hydrokinetic Turbine produced a Cp (Coefficient of power) value of 0.114 - 0.226 and a TSR (Tip Speed ​​Ratio) of 1.550 - 1.775. The performance of the Savonius Tornado Helical Hydrokinetic Turbine with end plate D / 2 was significantly higher than the Savonius Hydrokinetic Turbine, with an increase in Cp value of 11% and TSR of 12.6%. The Savonius Tornado Helical Hydrokinetic Turbine with end plate 3D / 4 increased the Cp and TSR values ​​by 6.6% and 10%. While the Savonius Tornado Helical Hydrokinetic Turbine with end plate 4D / 4 was able to increase the Cp value by 0.4% and TSR by 2.4%.